2007
DOI: 10.1089/scd.2006.0110
|View full text |Cite
|
Sign up to set email alerts
|

Human Heart, Spleen, and Perirenal Fat-Derived Mesenchymal Stem Cells Have Immunomodulatory Capacities

Abstract: Mesenchymal stem cells (MSCs) have important tissue repair functions and show potent immunosuppressive capacities in vitro. Although usually isolated from the bone marrow, MSCs have been identified in other tissues, including the skin and liver. In the present study, we isolated and characterized MSCs from human heart, spleen, and perirenal adipose tissue. MSCs from these different tissue sites were similar to those derived from bone marrow in that they expressed comparable levels of the cell-surface markers C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 28 publications
4
115
1
1
Order By: Relevance
“…Many subsequent studies have demonstrated that, umbilical cord and heart derived MSCs expressed identical levels of surface antigens such as CD90, CD44, CD105 and CD73. The present immunophenotyping pattern of MSCs derived from umbilical cord and human heart were found to be consistent with the reports of other groups (Hoogduijn et al 2007;Park et al 2007;Bai et al 2007). In addition, ) between experimental groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Many subsequent studies have demonstrated that, umbilical cord and heart derived MSCs expressed identical levels of surface antigens such as CD90, CD44, CD105 and CD73. The present immunophenotyping pattern of MSCs derived from umbilical cord and human heart were found to be consistent with the reports of other groups (Hoogduijn et al 2007;Park et al 2007;Bai et al 2007). In addition, ) between experimental groups.…”
Section: Discussionsupporting
confidence: 92%
“…we have also demonstrated that MSCs derived from two different sources have the ability to undergo multilineage mesenchymal differentiation such as osteogenic and adipogenic differentiation (Can and Balci 2011;Hoogduijn et al 2007). Ion channels play a major role in cellular electrophysiological activities by regulating the potential of membranes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The therapeutic benefits of BMMSCs is now established in several injury and disease models and preliminary data from clinical trials further confirm these claims [2]. In the recent past, several research groups have also identified mesenchymal stem-like populations from different post-natal and pre-natal tissues exhibiting tri-lineage differentiation potential (into osteogenic, adipogenic and chondrogenic lineages) [3,4]. These studies promise an easily accessible mesenchymal stem cell alternative to bone marrow.…”
Section: Introductionmentioning
confidence: 81%
“…ASCs have been demonstrated to exhibit immunosuppressive effects both in vitro and in vivo and may contribute to a reduction in local inflammation through the secretion of soluble factors of the Interleukin 6 (IL-6) family [17][18][19][20]. IL-6 may have a random role in inflammation depending of the microenvironnement.…”
Section: Cd25mentioning
confidence: 99%